The impact of the comprehensive treatment of the pneumoconiosis combined with the chronic obstructive pulmonary disease on some intoxication indicators in ore mining and iron and steel industry workers (Environment & Health, 2021)
Objective:We studied the efficiency of the comprehensive treatment of ore mining and iron and steel industry workers having the pneumoconiosis combined with chronic obstructive pulmonary disease in terms of intoxication indicators as an assessment of measures aimed at treatment and prevention of this occupational pulmonary pathology.Results: It was established that conducted treatment in the patients, ore mining and iron and steel industry workers with the use of bronchodilator, mucoregulator, anti-inflammatory agent of a complex vitamin medication, as well as sessions of hyperbaric oxygenation at 1.3 atm led to a decrease in the activity of inflammation processes with regard to the content in the peripheral blood of the total number of leukocytes, their stab and segmented subpopulations, and a decrease in most intoxication indices: the leukocytic index of intoxication, the granulocytic-agranulocytic index, the general index of intoxication, the sinistroposition index, the index of the ratio of leukocytes to erythrocyte sedimentation rate, which indicates a decrease in the systemic inflammation activity with the simultaneous suppression of intoxication phenomena. In comparison with the patients with other occupational lung pathology, the comprehensive treatment led to a more significant decrease in the content of segmented and stab leukocytes, as well as the main integral intoxication indices: the leukocytic index of intoxication, the granulocytic-agranulocytic index, and the general index. Thus, the comprehensive treatment of ore mining and iron and steel industry workers having the pneumoconiosis combined with the chronic obstructive pulmonary disease is an important link in the system of measures aimed at treatment and prevention ofthis occupational pulmonary pathology.Conclusions: In the ore mining and iron and steel industry workers having the pneumoconiosis combined with the chronic obstructive pulmonary disease,the comprehensive treatment with the use of bronchodilator, mucoregulator, nebulizer-administered anti-inflammatory agent, a complex vitamin B medication administered intramuscularly, as well as sessions of hyperbaric oxygenation led to an improvement in some inflammation indicators and intoxication indices which is a predictor of a positive course of the disease. The assessment of the results of the conducted comprehensive treatment of the workers indicates a significant positive dynamics of intoxication processes and makes it possible to regard this treatment as an important link in the system of measures aimed at treatment and preventionofthisoccupational pulmonary disease.
Keywords: pneumoconiosis; chronic obstructive pulmonary disease; workers; intoxication